1973
DOI: 10.1017/s0033291700049618
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine metabolism in affective illness: the effect of tryptophan administration

Abstract: SYNOPSISL-tryptophan 50 mg/kg was administered orally to patients suffering from either unipolar or bipolar affective illness, and the concentration of 5-hydroxyindol-acetic acid estimated in their cerebrospinal fluid eight hours later. There was no significant difference between the patient groups or between these and patients with neurological disease. These findings suggest a reduced neuronal activity in the 5-hydroxytryptaminergic system in some depressed patients rather than an absolute deficiency of tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Its presence in the cisternal rather than in the lumbar samples suggests that it reflects changes in the metabolism of 5HT with age, and not changes in the activity of the transport system which removes 5HIAA from the CSF. This view is supported by data from the study of Ashcroft et al 16 They found a quadratic relationship between lumbar CSF 5HIAA and age, very similar to that in fig 2, but only after the patients had received a load of tryptophan. If the quadratic relationship is due to a similar relationship between 5HT metabolism and age, then variation in one of two factors is presumably responsible, either the brain tryptophan content, or the activity of tryptophan hydroxylase.…”
Section: Age Differencesmentioning
confidence: 52%
“…Its presence in the cisternal rather than in the lumbar samples suggests that it reflects changes in the metabolism of 5HT with age, and not changes in the activity of the transport system which removes 5HIAA from the CSF. This view is supported by data from the study of Ashcroft et al 16 They found a quadratic relationship between lumbar CSF 5HIAA and age, very similar to that in fig 2, but only after the patients had received a load of tryptophan. If the quadratic relationship is due to a similar relationship between 5HT metabolism and age, then variation in one of two factors is presumably responsible, either the brain tryptophan content, or the activity of tryptophan hydroxylase.…”
Section: Age Differencesmentioning
confidence: 52%
“…Furthermore the negligible increase in brain 5-HIAA found when tryptophan was given to rats with decreased brain 5-HT may explain why the concentration of 5-HIAA in the CSF did not rise when L-tryptophan (2 to 3 g in divided doses) was given to a small group of depressives but did in other subjects (Bowers, 1970). This difference was not found when a somewhat larger single dose was given in another study (Ashcroft, Crawford, Cundall, Davidson, Dobson, Dow, Eccleston, Loose & Pullar, 1973).…”
Section: Discussionmentioning
confidence: 95%
“…Previous research reported that tryptophan concentration in CSF reflects Trp content in brain tissue [14,49,58] and that the concentration of 5-HIAA in the lumbar CSF reflects the turnover of 5-HT in the central nervous system [2,13,14,20,39,57]. Still debated is the origin of tryptophan metabolites via serotonin in CSF.…”
Section: Discussionmentioning
confidence: 99%